Senolytics: Eliminating Senescent Cells and Alleviating Intervertebral Disc Degeneration - Wu, Yuhao; Shen, Shiwei; Shi, Yifeng; Tian, Naifeng; Zhou, Yifei; Zhang, Xiaolei (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IVDD) is the main cause of cervical and lumbar spondylosis. Over the past few years, the relevance between cellular senescence and IVDD has been widely studied, the senescence-associated secretory phenotype (SASP) produced by senescent cells is found to remodel ECM metabolism and destruct homeostasis. Elimination of senescent cells by senolytics and suppression of SASP production by senostatics are effective strategies to alleviate degenerative diseases including IVDD. Here, we review the involvement of senescence in the process of IVDD; we also discuss the potential of senolytics on eliminating senescent disc cells and alleviating IVDD; finally, we provide a table listing senolytic drugs and small molecules, aiming to propose potential drugs for IVDD therapy in the future.